Sintetis secara Semi Kontinyu Biosurfaktan Ester Sorbitol Oleat Menggunakan Lipase Getah Pepaya Imobil - Suhardi Suhardi; Tranggono Tranggono; Pudji Hastuti; M. Muchalal (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2006)
Study on synthesis of sorbitol oleiate ester biosurfactan using Carica papaya latex immobilized-hpase as catalyst was caned out using oleic acid as a raw material. In the first step, process optimization for biosurfactan production was done with Carica papaya latex immobilized-lipase as acatalyst using a semi continuous methods. Lipase from Carica papaya latex was extracted using phosphate buffer pH 7.3 containing NaCI 0.1M then precipitated with addition of ammonium sulphate. Furthermore, the precipitated enzyme was solubilized in phosphate buffer pH 7.3, immobilized on Na-alginat (3%) and dried in freeze drier. Some variables for reaction were studied consisting of water concentration (20, 40, 60%), silica gel (0, 60, 120%) and reaction time (24,48,72 hours) with lipase concentration of 10%, and incubated at 45°C for those determined times and the acid value was monitored. In the second step, production of biosurfactant was also carried out using the semi-continuous methods, oleic acid and sorbitol were used as reactans and immobilzed-lipase of Carica papaya latex as a catalyst. Product fungsional properties were also determined including hydroxyl value, refraction index, melting point, fatty acid composition and HLB ( hydrophylic-lipophylic balance) value, surface tension and emulsifier characteristics. Result showed that : semi continuous production of sorbitol fatty acid ester with feed rate 0.1 ml per minute, temperature 45°C, 10% immobilized-lipse of Carica papaya latex, water: sorbitol ratio (40.16%), silica gel: water ratio (63.66%), sorbitol : oleic acid ratio (1:3 mol), incubation time 41.37 hours, resulted 54.96% product. The product characteristics were as follows : sorbitol oleiate acid ester content 70%, rendement 60%, hydroxil value 57 mg KOH/g, melting point 165°C, refractive index 1.4590, HLB value 7.5, surface tension 31.83 dyne/cm, capacity to keep emulsion (W/O) stability 140 minutes.